Experimental investigation on flow boiling pressure drop of R-290 and R-600a in a horizontal small tube. (December 2017) - de Oliveira, Jeferson Diehl; Copetti, Jacqueline Biancon; Passos, Júlio César
Highlights: The pressure drop is measured using R-290 and R-600a. The effect of mass flux, heat flux and quality conditions is investigated. The influence of flow patterns on the pressure drop is observed. Frictional pressure drop results are compared to predicted correlations. Abstract: Pressure drop for propane and isobutane were performed in a horizontal small tube of stainless steel with 1.0 mm inner diameter. The tests were conducted at mass fluxes from 240 to 480 kg m −2 s −1 and heat fluxes from 5 to 60 kW m −2 at 25 °C saturation temperature. The effect of flow patterns, mass flux, vapour quality and heat flux are discussed. Strong influence of mass flux and vapour quality on pressure drop was found. The comparisons of experimental data with predicted value proposed by existing correlations available in literature for pressure drop are analyzed.